Strengthening AI-Based Content Management System (CMS) Competencies for Indonesian Vocational Students and EEIEF Maria Nazare Viena as Provisions for Facing the Global Digital Work World - Muhlis Fajar Wicaksana; Dewi Kusumaningsih; Pardyatmoko Pardyatmoko; Citra Trihandayani; Wahyu Setiawati; Paulo Vitor da Silva Santiago (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2025)
In the current rapid global digital era, mastering AI-assisted digital branding and automated technical orchestration is an urgent requirement for vocational students, which can be strategically upgraded through project-based AI-Content Management System (CMS) training. Public and vocational institutions face a critical gap where students lack structured skills in managing digital platforms regularly and systematically, making traditional theoretical IT approaches ineffective for global workforce readiness. This international community service aims to resolve this issue by strengthening AI-based CMS competencies among Indonesian vocational students and EEIEF Maria Nazare Viena. The implementation method included socialization, digital literacy workshops, practical AI-tool application (action), intensive mentoring, and rubrics-based evaluations of student participants using pre-test and post-test instruments. The results revealed an 85% increase in students' cognitive, practical, and systematic platform management skills, supported by high student enthusiasm, cross-institutional academic networks, and institutional facility access, although slightly hindered by initial technical adjustments and budget management. Ultimately, the sustainability of this initiative is secured through the establishment of an online creative community forum and school-adopted digital manuals.